SIMILARITIES AND DIFFERENCES IN JAPANESE AND VIETNAMESE BUSINESS STYLES = Tương đồng và khác biệt trong văn hóa kinh doanh Nhật – Việt - Trần, Ngọc Việt Hoài (2020)
This thesis deals with similarities and differences in Japanese and Vietnamese business styles. The objectives of the study are to investigate the similarities and differences in some management practices and beliefs between Japanese and Vietnamese companies and to give explanations to some of them based on cultural knowledge reviewed from previous research. A survey questionnaire was designed for Japanese and Vietnamese businesspeople who have experience working in Japanese – Vietnamese business environment. The data analyzed from the questionnaire is employed to figure out the similarities and differences in business styles of companies from two countries. The first part of the questionnaire require personal information of the respondents. The second part is composed of 6 questions designed to explore the styles companies in Japan and Vietnam apply in daily management practices. The results demonstrate significant similarities and differences in the ways Japanese and Vietnamese businesspeople conduct business and run the organizations. Some findings appear to be contrast to or difficult to explain based on reviewed literature which proves the dynamics of culture. The study hopes to bring helpful findings for people concern and raise important problems for further research